Reform and Codification of Islamic Family Law in Turkey: From The Ottoman Law of Family Rights to the Turkish Civil Code of 1926 - Zikry Rahmatillah; Ziyad Alrawasdeh; Rahmat Tarmizi; Aulil Amri; Noor Fadillah Hayatusyifa; Firli Jundy Liza; Nur Lizawati (An-Nisa: Journal of Islamic Family Law, 2025)
The reform of Islamic family law is a strategic issue in response to social, cultural, and legal justice changes in Muslim countries. Turkey became one of the most prominent examples of radical reforms to its family law through the transition from the fiqh system of the Hanafi school of fiqh and The Ottoman Law of Family Rights (1917) to the Turkish Civil Code (1926) which adopted the Swiss Civil Code and affirmed the separation between religion and state. This study aims to analyze the process of reform and codification of Islamic family law in Turkey and its implications for the structure and substance of family law. The research method used is qualitative descriptive with a literature review approach to books, scientific articles, and relevant laws and regulations. The results show that family law reform in Turkey has led to fundamental changes, including the prohibition of polygamy, the equality of the rights of men and women in divorce and inheritance, and the strengthening of legal protection for women and children within the framework of secular civil law. These findings show that the reform of family law in Turkey is a form of adaptation of Islamic law to the modern state system without completely negating Islamic moral values. Based on these results, this study recommends that Muslim countries that carry out family law reforms consider a contextual and gradual approach, while maintaining a balance between the principles of justice, protection of human rights, and Islamic values that live in society.